Fighting Australia's Cold War: the nexus of strategy and operations in a multipolar Asia, 1945-1965 - Dean, Peter J. (Peter John), 1974-; Moss, Tristan (College teacher) (Australian National University Press, 2021)
In the first two decades of the Cold War, Australia fought in three conflicts and prepared to fight in a possible wider conflagration in Southeast Asia and the Pacific. In Korea, Malaya and Borneo, Australian forces encountered new types of warfare, integrated new equipment and ideas, and were part of the longest continual overseas deployments in Australia's history. Working closely with its allies, Australia also trained for a large conventional war in Southeast Asia, while a significant percentage of the defence force guarded the Papua New Guinea-Indonesian border. At home, the Defence organisation grappled with new threats and military expansion, while the Australian Security Intelligence Organisation defended the nation from domestic and foreign threats. This book examines this crucial part of Australia's security history, so often overlooked as merely a precursor to the Vietnam War. It addresses key questions such as how did Australia achieve its security goals at home and in the region in this new Cold War environment? What were the experiences of the services, units and individuals serving during in Southeast Asia? How did this period shape Australia's defence for years to come?